Synthesis of Deoxybenzoins Using Microwave Irradiations under Solvent Free Condition - KUMAR, SURESH; LAMBA, M.S.; MAKRANDI, J.K. (Asian Journal of Chemistry, 2010)
Phenols on reaction with arylacetic acid in the presence of polyphosphoric acid (PPA) under microwave irradiation and solvent free condition give deoxybenzoins directly in high yields.